New combinations and typification of Mediterranean Oeosporangium (Pteridaceae: Cheilanthoideae) - Arana, Marcelo D.; Moreno Saiz, Juan Carlos (Phytotaxa, 2020)
In this contribution the following new nomenclatural combinations for the natural hybrid taxa of Oeosporangium (Pteridaceae: Cheilanthoideae) occurring in the western Mediterranean basin and Canary Islands are proposed: Oeosporangium × ibericum (Rasbach & Reichst.) Arana & Moreno-Saiz, Oeosporangium × insulare (Rasbach & Reichst.) Arana & Moreno-Saiz, Oeosporangium × malacitense (Rasbach & Reichst.) Arana & Moreno-Saiz, Oeosporangium × marchettianum (Rasbach, Reichst. & Schneller) Arana & Moreno-Saiz, Oeosporangium × prototinaei (Rasbach, Reichst. & Schneller) Arana & Moreno-Saiz, Oeosporangium × teneriffae (Rasbach & Reichst.) Arana & Moreno-Saiz and Oeosporangium × tolocense (Rasbach, Reichst. & Schneller) Arana & Moreno-Saiz. Also the name Oeosporangium pulchellum is lectotypified.